Switch from premixed insulin analogue to degludec-liraglutide combination: a CGM study - Kravos Tramšek, Nika Aleksandra; Koceva, Andrijana; Krajnc, Mitja (Frontiers in Endocrinology, 2025)
IntroductionBasal insulin with glucagon-like peptide-1 receptor agonist could be preferred over premixed insulin for intensification in type 2 diabetes due to better glycemic control, lower hypoglycemia risk, and favorable effects on body weight. Comparative data on premixed insulin and the combination of degludec and liraglutide (iDegLira) are limited.MethodsWe conducted a 24-week single-arm prospective study to evaluate the impact of iDegLira compared to premixed insulin on the regulation of diabetes and glucovariability using continuous glucose monitoring (CGM), HbA1c, and anthropometric measurements. A total of 37 participants with type 2 diabetes (20 male and 17 female, aged 70.2 ± 10.0 years with BMI 31.0 (28.0-34.0) kg/m2 and duration of diabetes for 15.2 ± 7.7 years) were switched from premixed insulin treatment to iDegLira. The primary outcome was the change in HbA1c. Secondary outcomes included change in time in range (TIR) from baseline to 6 months, change in time below range (TBR), change in nocturnal hypoglycemia, glucovariability, insulin dose and body weight.ResultsWe observed improved glycemic control on iDegLira with improvement of average fasting glucose (6.92 ± 1.64 vs. 8.25 ± 2.2 mmol/l; p<0.031), HbA1c (7.10 ± 0.7% vs. 7.39 ± 0.7% p=0.045) and TIR (71.2 ± 17.2% vs. 64.3 ± 18.0; p=0.027). These results were accompanied by a nearly halved total daily insulin dose (-21 units/day, p<0.001) and a modest reduction of body weight.DiscussioniDegLira improved glycemic control, resulting in a lower HbA1c and higher TIR, alongside beneficial effects on body weight and total daily insulin doses. While numerical reductions in hypoglycemia did not reach statistical significance, treatment was not associated with an increased risk of hypoglycemia. iDegLira can be an efficient and safe treatment option, providing simplified treatment with improved glycemic control.